Users’ perception on the information security policy of the institutions of higher learning - Sharif, Haniza; Ismail, Zuraini; Masrom, Maslin (2009)
Securing information is essential for safeguarding the organization business operations as information is a business asset to any organization including education sector.One of the most imperative information security (InfoSec) controls identified is InfoSec policy, a direction-giving document.The purpose of this study is to investigate the user awareness, understanding and acceptance of InfoSec policy in the Malaysian’s Institutes of Higher Learning.Survey questionnaires had been distributed to graduate students and non-IT staff of Universiti Teknologi Malaysia (UTM),International Campus, Kuala Lumpur.The result of this study had perceived consistent agreeable behaviors of the InfoSec policy within UTM.